A high-conductivity polyanion positive electrode material and a preparation method thereof and a vehicle

By generating carbon nanotube structures on the surface of polyanionic materials, the problem of poor conductivity of polyanionic positive electrode materials is solved, and high conductivity and good cycling performance are achieved, which is suitable for large-scale production and commercial applications.

CN118645620BActive Publication Date: 2025-01-03ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411096032.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-01-03
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The existing preparation methods of polyanionic cathode materials are difficult to apply to large-scale production, and the material has poor electrical conductivity, which is not conducive to electron transfer and electrolyte penetration, affecting the energy density and cycling performance of the battery.

Method used

The polyanionic material is coated with carbon nanotubes (CNT) structural layer, and carbon nanotubes are generated at high temperatures through inert gas to form highly conductive polyanionic positive electrode materials, using ferrocene derivatives and 3,5-dioxide Methyl-1,2,4-triazole is used as a carbon source material to generate a carbon nanotube structure with high conductivity.

Benefits of technology

It improves the rate performance and cycling performance of the battery, reduces the amount of conductive agent, improves the transmission of ions and electrons, enhances the permeability of the electrolyte, and is suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645620B_ABST
    Figure CN118645620B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion batteries, and specifically to a highly conductive polyanion positive electrode material, a preparation method thereof, and a vehicle. The present invention provides a preparation method of a highly conductive polyanion positive electrode material, wherein a ferrocenyl compound, a camphoryl compound, and the like are used as carbon source materials, and a carbon nanotube structure layer is formed on the surface of a polyanion material as a matrix, thereby preparing a highly conductive polyanion positive electrode material. When the highly conductive polyanion positive electrode material is used in the preparation of a sodium ion battery, one-dimensional nanofibers are interconnected to form a unique three-dimensional network structure, which improves the transmission of ions and electrons, prevents the polyanion nanoparticles from being crushed and aggregated during the de-sodiumization and sodiumization processes, and the pores generated during the reaction process are conducive to the penetration of the electrolyte. At the same time, the preparation method of the highly conductive polyanion positive electrode material has a simple process, is suitable for large-scale production, and has good application in the field of sodium ion batteries for electric vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a highly conductive polyanion positive electrode material and a preparation method and a vehicle thereof. Background Art

[0002] Sodium-ion batteries (SIBs) have attracted great attention in medium- and large-scale energy storage base stations due to their abundant resources, low cost, and similar properties to lithium. The ionic radius of sodium ions is larger than that of lithium ions, and their redox potential is slightly higher than that of lithium, resulting in their low power and low energy density. In recent years, great progress has been made in anode materials, but the inability to match suitable cathode materials remains the main obstacle to the commercial application of SIBs. Therefore, finding suitable cathode materials with high power capacity, long cycle life, and good safety remains a daunting challenge.

[0003] Positive electrode materials mainly include transition metal oxide compounds, polyanion compounds, Prussian blue analogs and organic materials. Polyanion positive electrode materials have attracted great interest due to their advantages such as cheap raw materials, safe use and great working potential. Among them, polyanion positive electrode materials have a stable 3D main skeleton structure due to the strong covalent bonding of oxygen atoms in polyanion polyhedra. More importantly, this open 3D framework can provide sufficient gap channels for sodium ion transport and buffer the severe volume changes during sodium ion insertion / extraction. However, this material structure is not conducive to electron transfer and electrolyte penetration. Therefore, in actual industrial production, too much conductive agent needs to be added, which not only increases the cost, but also reduces the content of the main material, thereby affecting its energy density; on the contrary, if the conductive agent is not enough, it will cause interface problems, the internal resistance of the battery will increase significantly, and the capacity will be greatly attenuated during the use of the battery, especially at high rates, and the cycle performance will be greatly reduced. Therefore, the structural optimization of polyanion materials is imminent.

[0004] The modification methods of polyanion cathode materials reported so far are mainly coating, etc. For example, the invention patent CN116960308B introduces a complex including bacterial cellulose, sodium carboxymethyl cellulose and chitosan in the precursor raw material mixing stage, and then further mixes, spray-dries and calcines to obtain a carbon-coated modified polyanion cathode material. The invention patent CN115939345B proposes a nitrogen-doped carbon-coated modified polyanion cathode material, which mixes the raw materials and obtains a polyanion cathode material precursor by spray drying, and obtains a nitrogen-doped carbon-coated one after calcination. The spray drying method used in the above invention patent can be seen, but the spray drying method is difficult to apply to large-scale production processes. Summary of the invention

[0005] The invention aims to solve the problem that the method for preparing polyanion positive electrode materials by the existing technology is difficult to apply to large-scale production process.

[0006] The object of the present invention is to provide a highly conductive polyanion positive electrode material, comprising: a polyanion material as a matrix and a carbon nanotube (CNT) structure layer in situ coated on the surface of the matrix.

[0007] Preferably, the mass of the carbon nanotubes accounts for 0.5wt%-2.0wt% of the total mass of the highly conductive polyanion positive electrode material.

[0008] Preferably, the polyanion material includes at least one of sodium iron phosphate (NaFePO4), sodium vanadium phosphate (Na3V2(PO4)3), sodium iron pyrophosphate (Na2FeP2O7), sodium fluorinated iron phosphate (Na2FePO4F), sodium vanadium fluorinated phosphate (Na3V2(PO4)2F3), and sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7).

[0009] Preferably, the polyanion material is sodium vanadium phosphate (Na3V2(PO4)3).

[0010] Preferably, the carbon nanotube structure layer is produced using ferrocenyl compounds and camphoryl compounds as raw materials.

[0011] Preferably, the ferrocenyl compound includes at least one of ferrocene and a ferrocene derivative.

[0012] Preferably, the ferrocene derivative has a ferrocene monocarboxylic acid group and an N-methyl monoethanolamine group.

[0013] Preferably, the camphor-based compound comprises camphor.

[0014] The present invention also provides a method for preparing a highly conductive polyanion positive electrode material, comprising the following steps:

[0015] The solid or liquid carbon source material is converted into a gaseous carbon source material, which is transported to the polyanion material by an inert gas. The gaseous carbon source material is used to generate carbon nanotubes on the surface of the polyanion material at high temperature to obtain a highly conductive polyanion positive electrode material.

[0016] Preferably, the carbon source material includes a ferrocenyl compound and a camphor-based compound.

[0017] Preferably, the ferrocenyl compound includes at least one of ferrocene and a ferrocene derivative.

[0018] Preferably, the camphor-based compound comprises camphor.

[0019] Preferably, the mass of the carbon nanotubes accounts for 0.5-2.0 wt % of the total mass of the highly conductive polyanion positive electrode material.

[0020] Preferably, the polyanionic material is at a temperature of 500-700°C.

[0021] Preferably, the carbon source material is at a temperature of 150-200°C.

[0022] Preferably, after the polyanion material is at a temperature of 500-700°C, the carbon source material is then heated to a temperature of 150-200°C.

[0023] Preferably, the polyanion material and the carbon source material are used in a mass ratio of 1-10:1-10.

[0024] Preferably, the inert gas includes at least one of nitrogen and argon.

[0025] Preferably, the flow rate of the inert gas is 20-100 sccm.

[0026] Preferably, the polyanion material is located in heating zone A, and the carbon source material is located in heating zone B. The heating zone A and the heating zone B are interconnected, and the end of the heating zone A is connected to the oil seal exhaust port, and the end of the heating zone B is connected to the inert gas inlet.

[0027] More preferably, the specific preparation steps of the highly conductive polyanion positive electrode material are as follows:

[0028] Weigh 70-90 parts of sodium vanadium phosphate by mass and put them into heating zone A, then weigh 10-40 parts of camphor and 8-20 parts of ferrocene by mass, mix them thoroughly and put them into heating zone B; then introduce inert gas at a flow rate of 20-100sccm through the inert gas inlet connected to the end of heating zone B. At the same time, heating zone A is heated to 500-700℃ at 5-10℃ / min and kept warm, and then heating zone B is opened at a preset temperature of 150-200℃ at a heating rate of 5-10℃ / min. At this time, the gaseous carbon source material begins to generate CNT on the surface of the polyanion, and after reacting for 5-12h, it is cooled with the furnace and sieved to obtain a highly conductive polyanion positive electrode material.

[0029] In one embodiment of the present invention, a ferrocene derivative is used instead of ferrocene to prepare a highly conductive polyanion positive electrode material.

[0030] Preferably, the specific preparation steps of the highly conductive polyanion positive electrode material are as follows:

[0031] Weigh 70-90 parts of sodium vanadium phosphate by mass and put them into heating zone A, then weigh 10-40 parts of camphor and 8-20 parts of ferrocene derivatives by mass, mix them thoroughly and put them into heating zone B; then introduce inert gas at a flow rate of 20-100sccm through the inert gas inlet connected to the end of heating zone B. At the same time, heating zone A is heated to 500-700℃ at 5-10℃ / min and kept warm, and then heating zone B is opened at a preset temperature of 150-200℃ at a heating rate of 5-10℃ / min. At this time, the gaseous carbon source material begins to generate CNT on the surface of the polyanion, and after reacting for 5-12h, it is cooled with the furnace and sieved to obtain a highly conductive polyanion positive electrode material.

[0032] Ferrocene derivatives are prepared from ferrocene and N-methylmonoethanolamine. When the ferrocene derivatives are used to prepare highly conductive polyanion cathode materials, and then the highly conductive polyanion cathode materials are assembled into a half-cell, the half-cell has good rate performance and cycle performance. Ferrocene derivatives may improve the electrochemical properties of the highly conductive polyanion cathode materials prepared by promoting the growth of CNTs and introducing N elements for doping modification, so that the half-cell assembled with the highly conductive polyanion cathode materials has good rate performance and cycle performance.

[0033] In one embodiment of the present invention, the preparation steps of the ferrocene derivative include:

[0034] Ferrocene monocarboxylic acid, dichloromethane, anhydrous pyridine and oxalyl chloride are mixed, heated for reaction, and purified to obtain ferrocene monocarboxylic acid chloride; N-methyl monoethanolamine, triethylamine and dichloromethane are added to the ferrocene monocarboxylic acid chloride, reacted at room temperature, hydrochloric acid is added for quenching, and the ferrocene derivative is purified.

[0035] Preferably, ferrocene monocarboxylic acid and dichloromethane are used in a ratio of 1-3 mmol:4-6 mL.

[0036] Preferably, ferrocene monocarboxylic acid and anhydrous pyridine are used in a molar ratio of 1-3:1-3.

[0037] Preferably, ferrocene monocarboxylic acid and oxalyl chloride are used in a molar ratio of 1-3:1-3.

[0038] Preferably, the reaction is carried out by heating to 40-60°C.

[0039] Preferably, ferrocene monocarbonyl chloride and N-methyl monoethanolamine are used in a molar ratio of 1-10:1-10.

[0040] Preferably, ferrocene monocarbonyl chloride and triethylamine are used in a molar ratio of 1-10:1-10.

[0041] Preferably, ferrocene monocarbonyl chloride and dichloromethane are used in a molar ratio of 1-10:800-1000.

[0042] Preferably, the concentration of hydrochloric acid is 1-5M.

[0043] Preferably, ferrocene monocarbonyl chloride and hydrochloric acid are used in a ratio of 1-10 mmol: 20-60 mL.

[0044] More preferably, the specific preparation steps of the ferrocene derivative are as follows:

[0045] After ferrocene monocarboxylic acid is dried in vacuum, ferrocene monocarboxylic acid, dichloromethane and anhydrous pyridine are mixed in a ratio of 1-3mmol:4-6mL:1-3mmol, and then oxalyl chloride is added while stirring, and the molar ratio of oxalyl chloride to ferrocene monocarboxylic acid is 1-3:1-3. Then, it is heated to 40-60℃ for reaction for 4-8h. After the reaction is completed, dichloromethane and oxalyl chloride are removed under reduced pressure, and then petroleum ether with a boiling range of 60-90℃ is added for reflux for 1-2h, and the volume ratio of petroleum ether to dichloromethane is 1-5:1-5. Then, it is filtered, and the petroleum ether is removed under reduced pressure again to obtain ferrocene monocarboxylic acid chloride.

[0046] Ferrocene monocarbonyl chloride, N-methyl monoethanolamine, triethylamine and dichloromethane are mixed in a molar ratio of 1-10:1-10:1-10:800-1000, stirred at room temperature for 10-18h, and then hydrochloric acid is added in a ratio of 20-60mL:1-10mmol of hydrochloric acid: ferrocene monocarbonyl chloride, and the concentration of hydrochloric acid is 1-5M. Then, it is extracted with dichloromethane, washed with saturated sodium chloride solution after extraction, and dried with anhydrous sodium sulfate. Dichloromethane is removed by vacuum decompression to obtain a crude product, and the crude product is purified by silica gel flash chromatography to obtain a ferrocene derivative.

[0047] In one embodiment of the present invention, 3,5-dimethyl-1,2,4-triazole is added during the preparation of the highly conductive polyanion positive electrode material.

[0048] Preferably, the specific preparation steps of the highly conductive polyanion positive electrode material are as follows:

[0049] Weigh 70-90 parts of sodium vanadium phosphate by mass and put them into heating zone A, then weigh 10-40 parts of camphor, 5-10 parts of 3,5-dimethyl-1,2,4-triazole and 8-20 parts of ferrocene derivatives by mass, mix them thoroughly and put them into heating zone B; then, introduce inert gas at a flow rate of 20-100sccm through the inert gas inlet connected to the end of heating zone B. At the same time, heating zone A is heated to 500-700℃ at 5-10℃ / min and kept warm, and then heating zone B is opened at a preset temperature of 150-200℃ at a heating rate of 5-10℃ / min. At this time, the gaseous carbon source material begins to generate CNT on the surface of the polyanion, and after reacting for 5-12h, it is cooled with the furnace and sieved to obtain a highly conductive polyanion positive electrode material. When a highly conductive polyanion cathode material is prepared by adding 3,5-dimethyl-1,2,4-triazole, and then the highly conductive polyanion cathode material is assembled into a half-cell, the half-cell has better rate performance and cycle performance. 3,5-dimethyl-1,2,4-triazole may further provide N elements and cooperate with ferrocene derivatives to form a nitrogen-doped carbon coating layer, thereby improving the performance of the highly conductive polyanion cathode material and facilitating the transmission of sodium ions, thereby improving the rate performance and cycle performance of the half-cell assembled with the highly conductive polyanion cathode material.

[0050] The invention also provides the application of the highly conductive polyanion positive electrode material in a battery. The prepared highly conductive polyanion positive electrode material is used to prepare a battery, and the battery has good rate performance and cycle performance.

[0051] The present invention also provides use of the battery in preparing electric vehicles.

[0052] Compared with the prior art, the present invention provides a method for preparing a highly conductive polyanion cathode material, which has a simple process and is suitable for large-scale commercial production. The present invention uses ferrocene derivatives, 3,5-dimethyl-1,2,4-triazole and camphor as carbon sources, and forms a carbon nanotube structure layer on the surface of the polyanion material as a matrix, thereby preparing a highly conductive polyanion cathode material, which overcomes the problems of poor conductivity of polyanion materials and being unfavorable for electron transfer and electrolyte penetration. The prepared highly conductive polyanion cathode material is used to prepare a battery, which will reduce the amount of conductive agent, improve the energy density of the battery, and have good rate performance and cycle performance. The battery connects one-dimensional nanofibers to each other into a unique three-dimensional network structure, improves the transmission of ions and electrons, prevents the crushing and aggregation of polyanion nanoparticles during the de-sodiumization and sodiumization process, and the pores generated during the reaction process are conducive to the penetration of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1The invention relates to the preparation process of highly conductive polyanion positive electrode materials.

[0054] Figure 2 This is the infrared spectrum of ferrocene derivatives.

[0055] Figure 3 is the resistivity of the electrode.

[0056] Figure 4 is the resistance of the electrode.

[0057] Figure 5 This is an electron microscope image of the electrode. DETAILED DESCRIPTION

[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] The experimental methods in the following examples, unless otherwise specified, are all conventional methods or conditions recommended by the manufacturer. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0060] The preparation process of highly conductive polyanion cathode materials can be found in Figure 1 In the figure, 1 is a polyanion material; 2 and 3 are carbon source materials, including ferrocenyl compounds and camphoryl compounds. The heating zone A and the heating zone B are interconnected, and the end of the heating zone A is connected to the oil seal exhaust port; the end of the heating zone B is connected to the inert gas inlet.

[0061] Example 1: Preparation of highly conductive polyanion positive electrode materials

[0062] Weigh 70 parts of Na3V2(PO4)3 by mass and add them to heating zone A, weigh 15 parts of camphor and 15 parts of ferrocene by mass, mix them thoroughly and put them into heating zone B; then, nitrogen is introduced into the inert gas inlet connected to the end of heating zone B at a flow rate of 40sccm, and at the same time, heating zone A is heated to 600℃ at 10℃ / min and kept warm, and then heating zone B is opened at a preset temperature of 180℃ at a heating rate of 10℃ / min. At this time, CNTs begin to form on the surface of Na3V2(PO4)3, and after 8 hours of reaction, they are cooled in the furnace and sieved to obtain highly conductive polyanion positive electrode materials.

[0063] Example 2: Preparation of highly conductive polyanion positive electrode materials

[0064] The difference between Example 2 and Example 1 is that Example 2 uses a ferrocene derivative to replace ferrocene.

[0065] The preparation steps of ferrocene derivatives are as follows:

[0066] 22mmol of ferrocene monocarboxylic acid was dried under vacuum at 50℃ for 1h and then cooled to room temperature. After the system was dehydrated and deoxygenated, 50mL of dichloromethane and 22.3mmol of anhydrous pyridine were added, and then 23.6mmol of oxalyl chloride was added while stirring. Then the temperature of the system was raised to 50℃, and the reaction was stirred for 4h. After the reaction was completed, dichloromethane and oxalyl chloride were removed under reduced pressure, and then 50mL of petroleum ether with a boiling range of 60-90℃ was added and refluxed for 1h. The mixture was filtered through a closed sand core funnel, the filtrate was collected, and the petroleum ether was removed by distillation under reduced pressure again to obtain ferrocene monocarboxylic acid chloride.

[0067] 5mmol of ferrocene monocarbonyl chloride was added dropwise to 7.5mmol of N-methylmonoethanolamine, 10mmol of triethylamine and 0.92mol of dichloromethane at 0°C, and then stirred at room temperature for 12h. Then 40mL of 1M hydrochloric acid was added to quench the reaction, followed by extraction with dichloromethane, which was then washed with a saturated sodium chloride solution and dried with anhydrous sodium sulfate, and then distilled under vacuum to remove dichloromethane to obtain a crude product, which was purified by silica gel flash column chromatography to obtain a ferrocene derivative.

[0068] Example 3: Preparation of highly conductive polyanion positive electrode materials

[0069] The difference between Example 3 and Example 2 is that the amount of the ferrocene derivative used in Example 3 is 20 parts.

[0070] The preparation of ferrocene derivatives is the same as in Example 2.

[0071] Example 4: Preparation of highly conductive polyanion positive electrode materials

[0072] The difference between Example 4 and Example 3 is that in Example 4, 3,5-dimethyl-1,2,4-triazole is further added during the preparation of the highly conductive polyanion positive electrode material.

[0073] The preparation of highly conductive polyanion positive electrode materials includes the following steps:

[0074] 70 parts of Na3V2(PO4)3 were weighed by mass and added to heating zone A, 15 parts of camphor, 5 parts of 3,5-dimethyl-1,2,4-triazole and 20 parts of ferrocene derivative were weighed by mass and mixed thoroughly and then put into heating zone B; then nitrogen was introduced into the inert gas inlet connected to the end of heating zone B at a flow rate of 40sccm, and at the same time, heating zone A was heated to 600℃ at 10℃ / min and kept warm, and then heating zone B was opened at a preset temperature of 180℃ at a heating rate of 10℃ / min. At this time, CNT began to form on the surface of the polyanion material, and after 8 hours of reaction, it was cooled with the furnace and screened to obtain a highly conductive polyanion positive electrode material.

[0075] Example 5: Preparation of highly conductive polyanion positive electrode materials

[0076] The difference between Example 5 and Example 4 is that the amount of 3,5-dimethyl-1,2,4-triazole used in Example 5 is 10 parts.

[0077] Comparative Example 1: Preparation of highly conductive polyanion positive electrode material

[0078] The difference between Comparative Example 1 and Example 2 is that the amount of the ferrocene derivative used in Comparative Example 1 is 5 parts.

[0079] Test Example 1: Infrared spectrum of ferrocene derivatives

[0080] from Figure 2 The ferrocene derivative can be seen at 1692 cm -1 The peak at 3104 cm -1 The peak at 1407cm may be the =CH stretching vibration peak; -1 The peak at may be the C=C stretching vibration peak.

[0081] Test Example 2: Rate Performance Test

[0082] 2.0wt% PVDF, 2.0wt% conductive agent and 96.0wt% highly conductive polyanion positive electrode material were selected to prepare the electrode sheet, which was then assembled into a half-cell for testing. The voltage window of the half-cell test was 2-3.5V, and the current density was 1C=80mAg -1 The conductive agent includes commercially available conductive carbon black.

[0083] The highly conductive polyanion positive electrode materials prepared in Examples 1-5 and Comparative Example 1 were assembled into half-cells according to the above steps, and cycled 5 times at different rates of 0.1C, 1C, and 5C, and finally returned to 1C for 5 cycles. The rate performance of the half-cell was tested, and the results are shown in Table 1.

[0084] Comparing Example 1 with Examples 2 and 3, it can be seen that the ferrocene derivative is used to prepare the high-conductivity polyanion positive electrode material, and the rate performance of the half-cell is good; it indicates that the ferrocene derivative may promote the growth of CNTs and introduce N elements for doping modification, thereby improving the rate performance of the half-cell prepared from the high-conductivity polyanion positive electrode material. Comparing Examples 2 and 3 with Comparative Example 1, it is further shown that the amount of ferrocene derivatives plays an important role in the preparation of high-conductivity polyanion positive electrode materials. The amount of ferrocene derivatives used in Comparative Example 1 is small, which is not conducive to the generation of CNTs, and the high-conductivity polyanion positive electrode material prepared therefrom has poor rate performance when assembled into a half-cell.

[0085] Comparing Examples 3, 4, and 5, it can be seen that further adding 3,5-dimethyl-1,2,4-triazole during the preparation of the highly conductive polyanion cathode material can also help improve the rate performance of the half-cell assembled with the highly conductive polyanion cathode material; 3,5-dimethyl-1,2,4-triazole may further provide N elements to cooperate with ferrocene derivatives to form a nitrogen-doped carbon coating layer, thereby improving the performance of the highly conductive polyanion cathode material, accelerating the transmission rate of sodium ions, and making the half-cell assembled with the highly conductive polyanion cathode material have better rate performance.

[0086] Table 1 Rate performance results

[0087]

[0088] Test Example 3: Cyclic Performance Test

[0089] The highly conductive polyanion positive electrode materials prepared in Examples 1-5 and Comparative Example 1 were assembled into half-cells according to the steps of Test Example 2. They were first activated at a rate of 0.2C for 5 cycles, and then cycled at a conventional rate of 1C for 400 cycles. The cycle performance of the half-cell was tested and expressed by the capacity retention rate. The results are shown in Table 2.

[0090] The capacity retention rate calculation formula is R=X1 / X2, where X1 is the gram capacity in the first test and X2 is the gram capacity after 400 cycles.

[0091] Comparing Example 1 with Examples 2 and 3, it can be seen that the capacity retention rate of the half-cell is higher when the ferrocene derivative is used to prepare the high-conductivity polyanion positive electrode material; this may be because the ferrocene derivative can promote the generation of CNTs and provide N elements, thereby improving the electrochemical properties of the high-conductivity polyanion positive electrode material, thereby making the half-cell have better cycle performance. Comparing Examples 2 and 3 with Comparative Example 1, it is further shown that the amount of ferrocene derivatives plays an important role in the preparation of high-conductivity polyanion positive electrode materials. The amount of ferrocene derivatives used in Comparative Example 1 is relatively small, which is not conducive to CNT generation, and the half-cell assembled with the high-conductivity polyanion positive electrode material prepared therefrom has poor cycle performance.

[0092] Comparing Examples 3, 4, and 5, it can be seen that further adding 3,5-dimethyl-1,2,4-triazole during the preparation of the highly conductive polyanion cathode material can also help improve the cycle performance of the half-cell; 3,5-dimethyl-1,2,4-triazole may further provide N elements and cooperate with ferrocene derivatives to stabilize the highly conductive polyanion cathode material, thereby enabling the half-cell to have better cycle performance.

[0093] Table 2 Cycle performance results

[0094]

[0095] Test Example 4: Electrode resistance and resistivity detection

[0096] The raw material pole piece was prepared with 2.0wt% PVDF, 2.0wt% conductive agent and 96.0wt% Na3V2(PO4)3; the pole piece of the present invention was prepared with 2.0wt% PVDF, 2.0wt% conductive agent and 96.0wt% high conductive polyanion positive electrode material prepared in Example 1. Then the resistance and resistivity of the pole piece were detected by two-probe method. The equipment used was Yuanneng Technology BER2300. The conductive agent includes commercial conductive carbon black.

[0097] The specific method of two-probe detection is as follows:

[0098] Place the electrode in the middle of the two-probe probe; let the two-probe probe give the electrode a pressure of 25MPa and measure its resistance R. The resistivity ρ is calculated by the formula ρ=R×S / L, where S is the area of ​​the two-probe probe, which is 153.94mm 2 , L is the thickness of the electrode, and the thickness is obtained in advance using a thickness gauge.

[0099] The resistivity results of the electrode are as follows: Figure 3 As shown in FIG. 1 , it can be seen that the electrode of the present invention has a lower resistivity than the electrode of the raw material; the resistance result of the electrode is as follows Figure 4As shown, it can be seen that the electrode sheet of the present invention has lower resistance than the electrode sheet of the raw material. It shows that the highly conductive polyanion positive electrode material prepared by the preparation method of the present invention can significantly improve the ion and electron transmission of the electrode sheet when used to prepare the electrode sheet, thereby reducing the amount of conductive agent used and improving the energy density of the battery.

[0100] Test Example 5: Electron Microscope Image of Electrode

[0101] The electrode piece of the present invention in Test Example 4 was further observed by scanning electron microscope. Figure 5 The middle left picture shows the overall morphology of the electrode of the present invention after being magnified 15,000 times. It can be seen that carbon nanotubes grow around the edge of large particles; Figure 5 The middle right picture is an enlarged picture of the carbon nanotube part. It can be seen that the carbon nanotubes in the pole piece of the present invention are long strips of carbon nanotubes, and the carbon nanotubes and the conductive agent added to the pole piece are evenly distributed.

[0102] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

Claims

1. A highly conductive polyanion positive electrode material comprising: A polyanion material is used as a matrix, and a carbon nanotube structure layer is in-situ coated on the surface of the matrix; the mass of the carbon nanotubes accounts for 0.5-2.0wt% of the total mass of the highly conductive polyanion positive electrode material; The polyanion material comprises at least one of sodium iron phosphate, sodium vanadium phosphate, sodium iron pyrophosphate, sodium fluorinated iron phosphate, sodium vanadium phosphate fluorinated, and sodium iron pyrophosphate; The carbon nanotube structure layer is produced from 3,5-dimethyl-1,2,4-triazole, ferrocenyl compounds and camphoryl compounds as raw materials; the ferrocenyl compounds include ferrocenyl derivatives, which have ferrocenylmonocarboxylic acid groups and N-methylmonoethanolamine groups; the camphoryl compounds include camphor; In the preparation of the highly conductive polyanion positive electrode material, a solid or liquid carbon source material is converted into a gaseous carbon source material, which is transported to the polyanion material by an inert gas, and the gaseous carbon source material is used to generate carbon nanotubes on the surface of the polyanion material at a high temperature to obtain the highly conductive polyanion positive electrode material; the carbon source material is camphor, 3,5-dimethyl-1,2,4-triazole and a ferrocene derivative, and in parts by weight, the polyanion material is 70-90 parts, the camphor is 10-40 parts, the 3,5-dimethyl-1,2,4-triazole is 5-10 parts and the ferrocene derivative is 8-20 parts; The specific preparation steps of ferrocene derivatives are as follows: after ferrocene monocarboxylic acid is vacuum dried, ferrocene monocarboxylic acid, dichloromethane and anhydrous pyridine are mixed in a ratio of 1-3mmol:4-6mL:1-3mmol, and then oxalyl chloride is added while stirring, and the molar ratio of oxalyl chloride to ferrocene monocarboxylic acid is 1-3:1-3, and then heated to 40-60℃ for reaction for 4-8h. After the reaction is completed, dichloromethane and oxalyl chloride are removed under reduced pressure, and then petroleum ether with a boiling range of 60-90℃ is added to reflux for 1-2h, and the volume ratio of petroleum ether to dichloromethane is 1-5:1-5, and then filtered, and the oxalyl chloride is removed under reduced pressure again. Oily ether to obtain ferrocene monocarbonyl chloride; mix ferrocene monocarbonyl chloride, N-methyl monoethanolamine, triethylamine and dichloromethane in a molar ratio of 1-10:1-10:1-10:800-1000, stir at room temperature for 10-18h, then add hydrochloric acid in a ratio of hydrochloric acid: ferrocene monocarbonyl chloride of 20-60mL:1-10mmol, and the concentration of hydrochloric acid is 1-5M; then extract with dichloromethane, wash with saturated sodium chloride solution after extraction, and dry with anhydrous sodium sulfate, remove dichloromethane under vacuum to obtain a crude product, and purify the crude product by silica gel flash chromatography to obtain a ferrocene derivative.

2. A highly conductive polyanion positive electrode material according to claim 1, characterized in that: The polyanion material is Na3V2(PO4)3.

3. The method for preparing a highly conductive polyanion positive electrode material according to claim 1, comprising the following steps: The solid or liquid carbon source material is converted into a gaseous carbon source material, which is transported to the polyanion material by an inert gas, and the gaseous carbon source material is used to generate carbon nanotubes on the surface of the polyanion material at a high temperature to obtain a highly conductive polyanion positive electrode material; the carbon source material includes a ferrocene-based compound and a camphor-based compound, and the ferrocene-based compound includes a ferrocene derivative; The mass of the carbon nanotubes accounts for 0.5-2.0wt% of the total mass of the highly conductive polyanion positive electrode material; The polyanion material and the carbon source material are used in a mass ratio of 1-10:1-10; the inert gas includes at least one of nitrogen and argon; The specific preparation steps of the ferrocene derivative are as follows: after ferrocene monocarboxylic acid is vacuum dried, ferrocene monocarboxylic acid, dichloromethane and anhydrous pyridine are mixed in a ratio of 1-3mmol:4-6mL:1-3mmol, and then oxalyl chloride is added while stirring, and the molar ratio of oxalyl chloride to ferrocene monocarboxylic acid is 1-3:1-3, and then heated to 40-60°C for reaction for 4-8h. After the reaction is completed, dichloromethane and oxalyl chloride are removed under reduced pressure, and then petroleum ether with a boiling range of 60-90°C is added to reflux for 1-2h, and the volume ratio of petroleum ether to dichloromethane is 1-5:1-5, and then filtered, and removed under reduced pressure again. petroleum ether to obtain ferrocene monocarbonyl chloride; ferrocene monocarbonyl chloride, N-methyl monoethanolamine, triethylamine and dichloromethane are mixed in a molar ratio of 1-10:1-10:1-10:800-1000, stirred at room temperature for 10-18h, and then hydrochloric acid is added in a ratio of hydrochloric acid: ferrocene monocarbonyl chloride of 20-60mL:1-10mmol, and the concentration of hydrochloric acid is 1-5M; then extracted with dichloromethane, washed with saturated sodium chloride solution after extraction, and dried with anhydrous sodium sulfate, and dichloromethane is removed by vacuum decompression to obtain a crude product, and the crude product is purified by silica gel flash chromatography to obtain a ferrocene derivative.

4. The preparation method according to claim 3, characterized in that: The polyanion material is at a temperature of 500-700°C; or, the carbon source material is at a temperature of 150-200°C; or, after the polyanion material is at a temperature of 500-700°C, the carbon source material is then heated to 150-200°C.

5. A battery comprising the highly conductive polyanion positive electrode material according to any one of claims 1-2.

6. Use of the battery as claimed in claim 5 in electric vehicles.